Preparation method of anti-pilling wear-resistant double-layer laminated fabric

By using graphene oxide fibers in the fabric, composite treatment with magnetic iron tetraoxide nano-microspheres and tannin acid, a raised structure is formed to improve wear resistance, and pure cotton fibers that have been sorted out by plasma, quaternary ammonium salt and microwave treatment are used in the inner layer, the problems of easy breakage and chemical residue in the prior art are solved, and the effects of anti-pilling, wear resistance, moisture absorption and antibacteriality are achieved.

CN119872010APending Publication Date: 2025-04-25南通和顺兴纺织集团有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411933623.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to support the layered structure of graphene oxide, resulting in the fiber being easily broken and chemical factors are easily retained during the preparation process, affecting the performance of the fabric.

Method used

Graphene oxide fiber is used as the outer layer, and a raised structure is formed through composite treatment with magnetic iron tetraoxide nano-microspheres and tannin acid to improve wear resistance; the inner layer is made of pure cotton fiber, which improves hygroscopicity and antibacteriality through plasma treatment, quaternary ammonium salt finishing and microwave treatment, and two layers of fabrics are connected through adhesive.

Benefits of technology

It achieves anti-pilling, wear-resistant, hygroscopic and antibacterial effects, improves the overall performance of the fabric, and reduces the impact of chemicals on the inner fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210957010000071
    Figure BDA0005210957010000071
Patent Text Reader

Abstract

The invention discloses a preparation method of an anti-pilling wear-resistant double-layer laminated fabric, and relates to the technical field of multi-layer fabrics. After graphene oxide and magnetic ferroferric oxide nano microspheres are compounded, tannic acid is added for complexing and agglomeration, the three materials are coated inside and outside a graphene oxide layered structure, the supporting effect is achieved, meanwhile, the iron oxide microspheres are firmly combined on the surface of graphene oxide fibers to form protrusions, and the magnetic synergistic effect of the protrusion structures and iron oxide is achieved; the efficient anti-pilling effect is achieved. Secondly, performing plasma treatment: bombarding the surface of the pure cotton fiber by using an ion beam to form a recess, and giving an electrostatic binding site to a quaternary ammonium salt surfactant; and then microwave treatment is utilized, so that part of hydrogen bonds form hydrophilic groups and a molecular main chain is broken to form cracks, a water absorption channel is opened to improve the moisture absorption effect, and quaternary ammonium salt is still grafted on the surface of the fiber to achieve an antibacterial effect. The double-layer laminated fabric prepared by the invention has the effects of antibiosis, moisture absorption, wear resistance and pilling resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabrics, and in particular to a method for preparing an anti-pilling and wear-resistant double-layer laminated fabric. Background Art

[0002] Traditional fabrics are usually made of natural fibers such as cotton, linen, and silk. Natural fibers usually have the advantages of being hygroscopic, breathable, and harmless to the body, but they are prone to wrinkling, deformation, and wear. Artificial fibers are chemical fibers made from polymers through chemical treatment and mechanical processing. Artificial fibers have more functionality and higher wear resistance, but they are not as skin-friendly and environmentally friendly as traditional natural fibers.

[0003] On this basis, the advantages of the two major types of fibers are combined to prepare a double-sided laminated fabric. Due to the excellent physical and chemical properties of graphene oxide, it has great development value in the field of fabrics. However, due to its lamellar structure, graphene oxide is very easy to agglomerate, so larger particle size particles will appear when preparing fibers. The large graphene oxide particles in the fibers will form stress concentration points, which are easy to break when stretched, reducing the product quality. How to support the layered structure of graphene oxide while taking into account the wear-resistant and anti-pilling effects is the research direction of the present invention. At the same time, minimizing the treatment of the inner layer of natural fibers by chemicals and preventing the residual chemical factors on the fabric from bringing certain negative effects are also the focus of the present invention. In view of the above problems, the present invention provides a method for preparing an anti-pilling and wear-resistant double-layer laminated fabric to solve the current problem. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an anti-pilling and wear-resistant double-layer laminated fabric to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an anti-pilling and wear-resistant double-layer laminated fabric, wherein the double-layer laminated fabric has a graphene oxide fiber fabric as an outer layer and a pure cotton fiber fabric as an inner layer;

[0006] The anti-pilling and wear-resistant double-layer laminated fabric is prepared by the following method:

[0007] (1) Weigh 3-5 parts of graphene oxide and add them to 50 parts of ethylene glycol, stir them magnetically at 200-600 r / min for 10-30 min at 25° C., ultrasonicate them at 3000 Hz for 30-60 min, then add 0.5-1.5 parts of sodium dodecylbenzene sulfonate, 0.3-1.5 parts of ferric chloride pentahydrate and 1.5-7.5 parts of sodium oxalate, continue to stir until a uniform suspension is formed, then continue to add 0.6-1 parts of tannic acid, continue to stir for 12-24 h, wash the collected precipitate with ethanol and deionized water alternately 3 times after centrifugation, add deionized water and ultrasonicate them at 3000 Hz for 30-60 min to obtain a composite solution;

[0008] (2) The composite solution and KCl-methanol solution are used as the inner layer solution and the receiving solution; the inner layer diameter of the coaxial needle is 500 μm, the thickness is 200 μm, and the outer layer diameter is 1000 μm; the inner layer of the coaxial needle is connected to the injection pump, and the outer layer is connected to the barometer; the injection pump is turned on, and the outer layer solution is injected into the receiving solution to obtain fibers, which are naturally dried at 25° C. for 24 hours to obtain graphene oxide fibers, which are then twisted and woven to obtain a 200 g / m 2 Outer fabric;

[0009] (3) The cotton fibers are subjected to a humidity conditioning treatment at 30° C. and 90% humidity for 24 hours, and then the wet cotton fibers are subjected to a plasma treatment at a power of 1.0-4.0 kW for 15-45 seconds, and then dried at 25° C. for 6 hours. A quaternary ammonium salt surfactant aqueous solution with a concentration of 2 wt% is used as a finishing liquid for immersion and rolling. The finished cotton fibers are subjected to a microwave treatment at a power of 200-600 W for 1-3 minutes, and then twisted and woven to obtain a 300 g / m 2 The inner layer fabric is connected with the outer layer by adhesive to form a double-layer laminated fabric.

[0010] Furthermore, the centrifugation condition in step (1) is 5000 r / min for 30-60 min.

[0011] Furthermore, in step (1), the volume ratio of the precipitate to the deionized water is 1:20.

[0012] Furthermore, the mass concentration of the KCl-methanol solution in step (2) is 3 mol / L.

[0013] Furthermore, in step (2), the flow rate of the inner layer solution is controlled to be 0.6 mL / min.

[0014] Furthermore, in step (2), the flow rate of the outer layer solution is controlled to be 0.1 mL / s by a barometer.

[0015] Furthermore, in step (2), the diameter of the graphene oxide fiber is 500-700 μm.

[0016] Furthermore, in step (3), the quaternary ammonium salt surfactant is N-dimethyl-N-12-alkylaminopropyltrimethoxysilane.

[0017] Furthermore, in step (3), the one-immersion-one-rolling method is to immerse at room temperature for 1 hour, drain and then spin dry until the rolling rate is 50%.

[0018] Furthermore, the adhesive in step (3) is epoxy AB glue.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The present invention uses graphene oxide fiber as an outer layer and pure cotton fiber as an inner layer to form a double-layer laminated fabric to achieve the effects of antibacterial, moisture absorption, wear resistance and anti-pilling.

[0021] Firstly, the outer layer is woven with graphene oxide fibers; as the outer layer of the fabric, the main goal is to resist pilling and wear resistance; after the graphene oxide is compounded with the magnetic ferroferric oxide nano-microspheres, tannic acid is added as a modifier, and the large number of phenolic hydroxyl groups at the end of the tannic acid provide binding sites for the graphene oxide and the ferroferric oxide microspheres. The three are complexed and agglomerated, not only coated on the layered structure of the graphene oxide, but also interspersed in the middle of the layered structure, playing a supporting role while making the iron oxide microspheres firmly bonded to the surface of the graphene oxide fibers to form protrusions, thereby achieving the purpose of wear resistance, and the protruding structure also increases a certain friction resistance, and works synergistically with the magnetic effect of iron oxide, so that the fabric can only pill under a larger friction force, thereby achieving a high-efficiency anti-pilling effect.

[0022] Secondly, the inner layer is woven with pure cotton fibers; as the inner layer of the fabric, considering the contact with the human skin surface, the fiber layer is mainly skin-friendly, moisture-absorbing and antibacterial, so soft and skin-friendly pure cotton fibers are used as the main raw materials, firstly through plasma treatment, the energy size is controlled to bombard the surface of the pure cotton fibers with ion beams to form depressions but without destroying the fiber structure; then the inner layer of pure cotton fibers are treated with quaternary ammonium salt surfactants, and the quaternary ammonium salts as cations are electrostatically bonded to the negatively charged cotton fibers in the depressions and are not easy to fall off; finally, microwave treatment is used, and polar molecules such as water and cellulose in the cotton fibers strongly absorb microwaves, generating a large amount of heat, causing some hydrogen bonds and molecular main chains to break, and generating pressure to cause cracks in the cotton fibers, which open channels for the absorption of water molecules inside the fibers, and the broken hydrogen bonds can produce more hydrophilic groups to improve the moisture absorption effect, while the quaternary ammonium salts are not affected and are still grafted on the fiber surface to play an antibacterial effect. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of an anti-pilling and wear-resistant double-layer laminated fabric prepared in the following examples are as follows:

[0025] Antibacterial property: The fabrics of the embodiment and the comparative example were cut into 200 mm × 200 mm square samples; the samples were tested for antibacterial property according to the national standard GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method"; bacterial species: Escherichia coli ATCC25922, Staphylococcus aureus ATCC6538.

[0026] Hygroscopicity: The fabrics of the embodiment and the comparative example were cut into 200mm×200mm square samples; the mass of the tested dry sample was W1, and then the sample was placed in an environment with a humidity of 65%, and the mass W2 was measured after standing for 48 hours. Finally, the mass W0 was measured after drying at 105°C for 3 hours, and the moisture absorption rate was calculated; moisture absorption rate = (W2-W0) / W0x100%.

[0027] Wear resistance: The fabrics of the embodiments and comparative examples were cut into 200 mm × 200 mm square samples; the samples were measured according to GB / T21196.3, and the samples were installed in the fixture of the Martindale abrasion tester to make a planar motion with a trajectory of the Lissajous curve. The abrasive used was standard 600 mesh water sandpaper, the nominal pressure was 9 kPa, and the abrasion times were 100, and the mass loss rate was calculated; the mass loss calculation formula was: X = (1-m1 / m2) × 100% (X—mass loss rate%; m1—original mass of fabric g; m2—mass of fabric after wear test g).

[0028] Anti-pilling property: the fabrics of the embodiment and the comparative example were cut into 200 mm×200 mm square samples; the samples were tested according to the fabric pilling grade (outer layer): the test was carried out with reference to GB / T4802.2-2008.

[0029] Example 1; (1) Weigh 3 parts of graphene oxide and add them to 50 parts of ethylene glycol. After magnetic stirring at 200 r / min for 10 min at 25°C, ultrasonicate at 3000 Hz for 30 min, add 0.5 parts of sodium dodecylbenzene sulfonate, 0.3 parts of ferric chloride pentahydrate and 1.5 parts of sodium oxalate, continue stirring until a uniform suspension is formed, then continue to add 0.6 parts of tannic acid, continue stirring for 12 h, centrifuge at 5000 r / min for 30 min, wash the collected precipitate alternately with ethanol and deionized water 3 times, mix the precipitate with deionized water in a volume ratio of 1:20, and ultrasonicate at 3000 Hz for 30 min to obtain a composite solution;

[0030] (2) The composite solution and the KCl-methanol solution with a mass concentration of 3 mol / L are used as the inner layer solution and the receiving solution; the inner layer diameter of the coaxial needle is 500 μm, the thickness is 200 μm, and the outer layer diameter is 1000 μm; the inner layer of the coaxial needle is connected to the injection pump, and the outer layer is connected to the barometer; the injection pump is turned on, the flow rate of the inner layer solution is controlled to 0.6 mL / min, and the flow rate of the outer layer solution is controlled to 0.1 mL / s by the barometer, and the outer layer solution is injected into the receiving solution to obtain a fiber, which is naturally dried at 25°C for 24 hours to obtain a graphene oxide fiber with a diameter of 500 μm, and then twisted and woven to obtain a gram weight of 200 g / m 2 Outer fabric;

[0031] (3) The cotton fiber is subjected to a humidity conditioning treatment at 30° C. and 90% humidity for 24 hours, and then the wet cotton fiber is subjected to a plasma treatment at a power of 1.0 kW for 15 seconds, and then dried at 25° C. for 6 hours. The cotton fiber is immersed and rolled using a 2 wt % N-dimethyl-N-12-alkylaminopropyl trimethoxysilane aqueous solution as a finishing liquid, that is, immersed at room temperature for 1 hour, drained, and then dried to a rolling rate of 50%; the finished cotton fiber is subjected to a microwave treatment at a power of 200 W for 1 minute, and then twisted and woven to obtain a 300 g / m 2 The inner layer fabric is connected with the outer layer by epoxy AB glue to form a double-layer laminated fabric.

[0032] Example 2; (1) Weigh 4 parts of graphene oxide and add them to 50 parts of ethylene glycol. After magnetic stirring at 400 r / min for 20 min at 25°C, ultrasonicate at 3000 Hz for 45 min, add 1 part of sodium dodecylbenzene sulfonate, 0.8 parts of ferric chloride pentahydrate and 4.5 parts of sodium oxalate, continue stirring until a uniform suspension is formed, continue to add 0.8 parts of tannic acid, continue stirring for 18 h, centrifuge at 5000 r / min for 45 min, and wash the collected precipitate alternately with ethanol and deionized water for 3 times. Mix the precipitate with deionized water in a volume ratio of 1:20, and ultrasonicate at 3000 Hz for 45 min to obtain a composite solution;

[0033] (2) The composite solution and the KCl-methanol solution with a mass concentration of 3 mol / L are used as the inner layer solution and the receiving solution; the inner layer diameter of the coaxial needle is 500 μm, the thickness is 200 μm, and the outer layer diameter is 1000 μm; the inner layer of the coaxial needle is connected to the injection pump, and the outer layer is connected to the barometer; the injection pump is turned on, the flow rate of the inner layer solution is controlled to 0.6 mL / min, and the flow rate of the outer layer solution is controlled to 0.1 mL / s by the barometer, and the outer layer solution is injected into the receiving solution to obtain a fiber, which is naturally dried at 25°C for 24 hours to obtain a graphene oxide fiber with a diameter of 600 μm, and then twisted and woven to obtain a gram weight of 200 g / m 2 Outer fabric;

[0034] (3) The cotton fiber is subjected to a humidity conditioning treatment at 30° C. and 90% humidity for 24 hours, and then the wet cotton fiber is subjected to a plasma treatment at a power of 2.5 kW for 30 seconds, and then dried at 25° C. for 6 hours. The cotton fiber is immersed and rolled using a 2 wt % N-dimethyl-N-12-alkylaminopropyl trimethoxysilane aqueous solution as a finishing liquid, that is, immersed at room temperature for 1 hour, drained, and then dried to a rolling rate of 50%; the finished cotton fiber is subjected to a microwave treatment at a power of 400 W for 2 minutes, and then twisted and woven to obtain a 300 g / m 2 The inner layer fabric is connected with the outer layer by epoxy AB glue to form a double-layer laminated fabric.

[0035] Example 3; (1) Weigh 5 parts of graphene oxide and add them to 50 parts of ethylene glycol. After magnetic stirring at 600 r / min for 30 min at 25°C, ultrasonicate at 3000 Hz for 60 min, add 1.5 parts of sodium dodecylbenzene sulfonate, 1.5 parts of ferric chloride pentahydrate and 7.5 parts of sodium oxalate, continue stirring until a uniform suspension is formed, and then continue to add 1 part of tannic acid. Continue stirring for 24 hours, centrifuge at 5000 r / min for 60 min, and wash the collected precipitate alternately with ethanol and deionized water for 3 times. Mix the precipitate with deionized water in a volume ratio of 1:20, and ultrasonicate at 3000 Hz for 60 min to obtain a composite solution;

[0036] (2) The composite solution and the KCl-methanol solution with a mass concentration of 3 mol / L are used as the inner layer solution and the receiving solution; the inner layer diameter of the coaxial needle is 500 μm, the thickness is 200 μm, and the outer layer diameter is 1000 μm; the inner layer of the coaxial needle is connected to the injection pump, and the outer layer is connected to the barometer; the injection pump is turned on, the flow rate of the inner layer solution is controlled to 0.6 mL / min, and the flow rate of the outer layer solution is controlled to 0.1 mL / s by the barometer, and the outer layer solution is injected into the receiving solution to obtain a fiber, which is naturally dried at 25°C for 24 hours to obtain a graphene oxide fiber with a diameter of 700 μm, and then twisted and woven to obtain a gram weight of 200 g / m 2 Outer fabric;

[0037] (3) The cotton fiber is subjected to a humidity conditioning treatment at 30° C. and 90% humidity for 24 hours, and then the wet cotton fiber is subjected to a plasma treatment at a power of 4.0 kW for 45 seconds, and then dried at 25° C. for 6 hours. The cotton fiber is immersed and rolled using a 2 wt % N-dimethyl-N-12-alkylaminopropyl trimethoxysilane aqueous solution as a finishing liquid, that is, immersed at room temperature for 1 hour, drained, and then dried to a rolling rate of 50%; the finished cotton fiber is subjected to a microwave treatment at a power of 600 W for 3 minutes, and then twisted and woven to obtain a 300 g / m 2 The inner layer fabric is connected with the outer layer by epoxy AB glue to form a double-layer laminated fabric.

[0038] Comparative Example 1; The difference between Comparative Example 1 and Example 2 is that step (2) is different, and step (3) is changed to: weigh 4 parts of graphene oxide and add them to 50 parts of ethylene glycol, add 0.8 parts of tannic acid after magnetic stirring at 400 r / min for 20 min at 25°C, continue stirring for 2 h, centrifuge at 5000 r / min for 45 min, and wash the collected precipitate alternately with ethanol and deionized water for 3 times, mix the precipitate with deionized water in a volume ratio of 1:20, and obtain a composite solution after ultrasonication at 3000 Hz for 45 min; the remaining steps are the same as Example 2.

[0039] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is different, and step (1) is changed to: weigh 4 parts of graphene oxide and add them to 50 parts of ethylene glycol, magnetically stir at 400 r / min for 20 min at 25°C, ultrasonicate at 3000 Hz for 45 min, then add 1 part of sodium dodecylbenzene sulfonate, 0.8 parts of ferric chloride pentahydrate and 4.5 parts of sodium oxalate, continue stirring until a uniform suspension is formed, centrifuge at 5000 r / min for 45 min, and wash the collected precipitate alternately with ethanol and deionized water for 3 times, mix the precipitate with deionized water in a volume ratio of 1:20, and ultrasonicate at 3000 Hz for 45 min to obtain a composite solution; the remaining steps are the same as Example 2.

[0040] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (3) is different, and step (3) is changed to: the cotton fiber is immersed and rolled with a 2wt% N-dimethyl-N-12-alkylaminopropyl trimethoxysilane aqueous solution as a finishing liquid, that is, immersed at room temperature for 1 hour, drained and then dried to a rolling rate of 50%; the finished cotton fiber is treated with a microwave power of 400W for 2min, and then twisted and woven to obtain a 300g / m 3 The inner layer and the outer layer are connected by epoxy AB glue to form a double-layer laminated fabric; the remaining steps are the same as in Example 2.

[0041] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (3) is different, and step (3) is changed to: the cotton fiber is subjected to a 24h humidity conditioning treatment at 30°C and 90% humidity, and then the wet cotton fiber is plasma treated at a power of 2.5kW for 30s, dried at 25°C for 6h, and a 2wt% N-dimethyl-N-12-alkylaminopropyltrimethoxysilane aqueous solution is used as a finishing liquid for one immersion and one rolling, that is, after immersion at room temperature for 1h, draining and then drying to a rolling rate of 50%; the finished cotton fiber is twisted and woven to obtain a 300g / m 2 The inner layer and the outer layer are connected by epoxy AB glue to form a double-layer laminated fabric; the remaining steps are the same as in Example 2.

[0042] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that step (3) is different, and step (3) is changed to: the cotton fiber is subjected to a humidity conditioning treatment at 30°C and 90% humidity for 24 hours, and then the wet cotton fiber is plasma treated at a power of 2.5kW for 30 seconds, dried at 25°C for 6 hours, and then the cotton fiber is microwave treated at a power of 400W for 2 minutes, and then twisted and woven to obtain a gram weight of 300g / m 2 The inner layer and the outer layer are connected by epoxy AB glue to form a double-layer laminated fabric; the remaining steps are the same as in Example 2.

[0043] Effect example

[0044] Table 1 below shows the performance analysis results of an anti-pilling and wear-resistant double-layer laminated fabric using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0045] Table 1

[0046]

[0047] From the comparison of the wear resistance experimental data of the embodiment and the comparative example, it can be found that the present invention first composites graphene oxide with magnetic ferroferric oxide nano-microspheres, and then adds tannic acid as a modifier. The large amount of phenolic hydroxyl groups at the end of tannic acid provide binding sites for graphene oxide and ferroferric oxide microspheres. The three are complexed and agglomerated, not only coated on the layered structure of graphene oxide, but also interspersed in the middle of the layered structure, playing a supporting role, while making the iron oxide microspheres firmly combined on the surface of graphene oxide fibers to form protrusions, thereby achieving the purpose of wear resistance. From the comparison of the pilling grade experimental data of the embodiment and the comparative example, it can be found that the protruding structure on the surface of graphene oxide fibers increases a certain friction resistance, and synergizes with the magnetic effect of iron oxide, so that the fabric can only pill under a large friction force, thereby achieving an efficient anti-pilling effect. From the comparison of the experimental data of the antibacterial property of the embodiment and the comparative example, it can be found that the present invention adopts soft and skin-friendly pure cotton fiber as the main raw material, firstly uses plasma treatment to control the energy size to bombard the surface of the pure cotton fiber with an ion beam to form a depression but does not destroy the fiber structure; then the inner layer of pure cotton fiber is sorted with a quaternary ammonium salt surfactant, and the quaternary ammonium salt as a cation is electrostatically combined with the cotton fiber with its own negative charge in the depression and is not easy to fall off, thereby playing an antibacterial effect; from the comparison of the experimental data of the antibacterial property of the embodiment and the comparative example, it can be found that the present invention uses microwave treatment, and polar molecules such as water and cellulose in the cotton fiber strongly absorb microwaves, generate a large amount of heat, cause partial hydrogen bonds and molecular main chains to break, and generate pressure to cause the cotton fiber to form cracks, and the cracks open the channel for the absorption of water molecules inside the fiber, and the broken hydrogen bonds can produce more hydrophilic groups to improve the moisture absorption effect.

[0048] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An anti-pilling and wear-resistant double-layer laminated fabric, characterized in that: The double-layer laminated fabric has a graphene oxide fiber fabric as an outer layer and a pure cotton fiber fabric as an inner layer; The anti-pilling and wear-resistant double-layer laminated fabric is prepared by the following method: (1) Weigh 3-5 parts of graphene oxide and add them to 50 parts of ethylene glycol, stir them magnetically at 200-600 r / min for 10-30 min at 25° C., ultrasonicate them at 3000 Hz for 30-60 min, then add 0.5-1.5 parts of sodium dodecylbenzene sulfonate, 0.3-1.5 parts of ferric chloride pentahydrate and 1.5-7.5 parts of sodium oxalate, continue to stir until a uniform suspension is formed, then continue to add 0.6-1 parts of tannic acid, continue to stir for 12-24 h, wash the collected precipitate with ethanol and deionized water alternately 3 times after centrifugation, add deionized water and ultrasonicate them at 3000 Hz for 30-60 min to obtain a composite solution; (2) The composite solution and KCl-methanol solution are used as the inner layer solution and the receiving solution; the inner layer diameter of the coaxial needle is 500 μm, the thickness is 200 μm, and the outer layer diameter is 1000 μm; the inner layer of the coaxial needle is connected to the injection pump, and the outer layer is connected to the barometer; the injection pump is turned on, and the outer layer solution is injected into the receiving solution to obtain fibers, which are naturally dried at 25° C. for 24 hours to obtain graphene oxide fibers, which are then twisted and woven to obtain a 200 g / m 2 Outer fabric; (3) The cotton fibers are subjected to a humidity conditioning treatment at 30° C. and 90% humidity for 24 hours, and then the wet cotton fibers are subjected to a plasma treatment at a power of 1.0-4.0 kW for 15-45 seconds, and then dried at 25° C. for 6 hours. A quaternary ammonium salt surfactant aqueous solution with a concentration of 2 wt% is used as a finishing liquid for immersion and rolling. The finished cotton fibers are subjected to a microwave treatment at a power of 200-600 W for 1-3 minutes, and then twisted and woven to obtain a 300 g / m 2 The inner layer fabric is connected with the outer layer by adhesive to form a double-layer laminated fabric.

2. The method for preparing the anti-pilling and wear-resistant double-layer laminated fabric according to claim 1, characterized in that: The centrifugation condition in step (1) is 5000 r / min for 30-60 min.

3. The method for preparing the anti-pilling and wear-resistant double-layer laminated fabric according to claim 1, characterized in that: The volume ratio of the precipitate to the deionized water in the step (1) is 1:

20.

4. The method for preparing the anti-pilling and wear-resistant double-layer laminated fabric according to claim 1, characterized in that: The mass concentration of the KCl-methanol solution in step (2) is 3 mol / L.

5. The method for preparing the anti-pilling and wear-resistant double-layer laminated fabric according to claim 1, characterized in that: In the step (2), the flow rate of the inner layer solution is controlled to be 0.6 mL / min.

6. The method for preparing the anti-pilling and wear-resistant double-layer laminated fabric according to claim 1, characterized in that: In the step (2), the flow rate of the outer layer solution is controlled to be 0.1 mL / s by a barometer.

7. The method for preparing the anti-pilling and wear-resistant double-layer laminated fabric according to claim 1, characterized in that: In the step (2), the diameter of the graphene oxide fiber is 500-700 μm.

8. The method for preparing the anti-pilling and wear-resistant double-layer laminated fabric according to claim 1, characterized in that: The quaternary ammonium salt surfactant in step (3) is N-dimethyl-N-12-alkylaminopropyltrimethoxysilane.

9. The method for preparing the anti-pilling and wear-resistant double-layer laminated fabric according to claim 1, characterized in that: In the step (3), the process of one dipping and one rolling is to dip the mixture at room temperature for 1 hour, drain the mixture, and then spin dry the mixture until the rolling rate is 50%.

10. The method for preparing the anti-pilling and wear-resistant double-layer laminated fabric according to claim 1, characterized in that: The adhesive in step (3) is epoxy AB glue.

Citation Information

Patent Citations

  • Yilon / cotton blended weft plain stitch knitted fabric and preparation method thereof

    CN106012260A

  • Antibacterial and deodorant fiber, fabric and preparation method of antibacterial and deodorant fiber

    CN118621593A